The Role and Special Significance of Private Entrepreneurship in the Development of Society - ogli, Muzaffarov Umidjon Ismoil; Sobirovna, Ergashova Nilufar (Research Parks Publishers, 2023)
This article discusses how now private enterprises can be created as legal entities and has property and personal non-property rights in their own name. The article also reveals the special significance of the emergence of legal entities in the current difficult time and their place in the life of society.